Science in the Kitchen-August 2022 : Do wars alone change the course of history? Or can a vegetable change it too? - Doğan, Murat (İstmag Magazin Gazetecilik, 2022)
All of us have taken history lessons in school at some point. Many, like me, found history fascinating and developed a love for it. Now, I want to ask you this: Can a vegetable change the course of history? If I say yes, I can almost hear you exclaiming, “Don’t talk nonsense, professor!”
Keywords: change the course of history; vegetable